Angle's classification and hypodontia, is there an association? - Afrah Kh Al-Hamdany; Ne'am R Al-Saleem; Aisha A Qasim (University of Mosul, College of Dentistry, 2007)
Aims: To find the association between different Angle's classes of malocclusion and to estimate the distribution of hypodontia according to gender, number of missing teeth and the site of the missing teeth. In addition, the heredity role in hypodontia was investigated. Materials and Methods: About 3415 subjects, 1750 females and 1665 males aging between 18-30 years were examined clinically in addition periapical radiographs were taken for each patient to exclude a possibility of impaction. A family history of hypodontia for each patient was taken (for father, mother, brothers and sisters). Then the sample was divided into 3 groups depending on Angle's classification of malocclusion. Results: No clear association was found between Angle's classes and hypodontia, females showed higher prevalence of hypodontia than males. Family history was obvious in patients with hypodontia. The upper lateral incisor was the most frequent absent tooth. Conclusions: No association was found between Angle's classification and hypodontia. The upper lateral incisor was the most frequent missing tooth. Maxilla was affected by hypodontia more than mandible. Females were affected more than males with very obvious effect of family history on hypodontia.